Comparative Assessment of Physical Development and Component Composition of the Body Weight of Sportswoman Participated in Gymnastics (Texas Journal of Multidisciplinary Studies, 2023)
The article considers a comparative assessment of the physical development and component composition of the body mass of female athletes involved in the types of gymnastics. Studies have shown specifically selected features that change under the influence of training loads, contribute to the formation of a harmonious figure and slender posture, and can be used in selective selection for practicing various types of gymnastics